Panel estimation for the impacts of population-related factors on CO2 emissions: A regional analysis in China. (July 2017) - Wang, Yanan; Kang, Yanqing; Wang, Juan; Xu, Linan
Highlights: We analyzed the impacts of population-related factors on CO2 emissions in China. Per capita consumption has significant impact on CO2 emissions. Aging population decrease emissions in central and western regions. Household size has a negative effect on CO2 emissions. Abstract: A large accumulation of carbon dioxide emission have attracted much attention recently. The existing researches mainly focused on such impact factors of carbon dioxide emission as population, economy, technology and others. However, there is little specific guidance for the subdivision of demographic factors. This paper employed STIRPAT (Stochastic Impacts by Regression on Population, Affluence and Technology) model to examine the impact of population size, per capita consumption, energy intensity, urbanization and aging population on CO2 emissions by adopting panel data of 30 provinces from 1997 to 2012. Taking the climate change as a control variable, we can get the result that the population size, per capita consumption and energy intensity have strong explanatory power on CO2 emissions in the three regions. The urbanization level has a positive influence on carbon emissions in the western region and has a negative effect in the central region, while it is not statistically significant in the eastern region. Aging population increases emissions in the eastern region, while decreases emissions in the central region and the western region.